2011
DOI: 10.1371/journal.pone.0021351
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Signalling Genes Are Regulated by Photoperiod in the Hypothalamus of F344 Rats

Abstract: Seasonal animals adapt their physiology and behaviour in anticipation of climate change to optimise survival of their offspring. Intra-hypothalamic thyroid hormone signalling plays an important role in seasonal responses in mammals and birds. In the F344 rat, photoperiod stimulates profound changes in food intake, body weight and reproductive status. Previous investigations of the F344 rat have suggested a role for thyroid hormone metabolism, but have only considered Dio2 expression, which was elevated in long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
92
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(99 citation statements)
references
References 42 publications
7
92
0
Order By: Relevance
“…However, the applicability of the present findings may be more generic rather than merely applicable to mammals that are normally associated with seasons, as most laboratory strains of rats have the potential to respond to photoperiods with physiological changes following olfactory bulbectomy (Nelson & Zucker 1981) or after manipulation of testosteronenegative feedback (Wallen et al 1987). Moreover, the F344 rat strain does show physiological responses to photoperiods in terms of food intake and body weight (Ross et al 2011) and increases in Dio2 expression in the ependymal layer following i.c.v. administration of TSH (Helfer et al 2013).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…However, the applicability of the present findings may be more generic rather than merely applicable to mammals that are normally associated with seasons, as most laboratory strains of rats have the potential to respond to photoperiods with physiological changes following olfactory bulbectomy (Nelson & Zucker 1981) or after manipulation of testosteronenegative feedback (Wallen et al 1987). Moreover, the F344 rat strain does show physiological responses to photoperiods in terms of food intake and body weight (Ross et al 2011) and increases in Dio2 expression in the ependymal layer following i.c.v. administration of TSH (Helfer et al 2013).…”
Section: Discussionmentioning
confidence: 82%
“…To investigate the signal transduction mechanism of the TSH receptor in the hypothalamic ependymal layer, we chose to utilise primary cell cultures of these cells from 10-day-old rat brains, as described by Prevot et al (2003). First, as found in other species, Tsh receptor mRNA expression was confirmed by in situ hybridisation in the hypothalamus of 10-day-old rats, confined to the cells adjacent to the third ventricle (Hanon et al 2008, Nakao et al 2008, Ross et al 2011, Herwig et al 2013. Using primary ependymal layer cell cultures prepared from 10-day-old rats, we investigated the signal transduction mechanism used by TSH receptors to transduce hormone binding in these cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raldh1 protein is transported along the length of the tanycyte fibres (Shearer et al, 2010), which have been shown to contact Agrp/Npy neurons in the hypothalamus (Coppola et al, 2007), potentially releasing RA immediately adjacent to the target cells. This novel pathway provides a new route by which TH may promote expression of neuronal Agrp to increase appetite (Varela et al, 2012) and may also provide a mechanism by which TH could increase Ghrh to promote growth (Ross et al, 2011). The potential also exists for this to be a mechanism by which TH controls neurogenesis given the recent finding of RA's control of cell proliferation in the neurogenic regions of the hypothalamus (Shearer et al, 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…The Dio2 gene encodes the enzyme that converts thyroxine (T4) into biologically active triidothyronine (T3), whereas Dio3 is responsible for degrading T4 and T3 to inactive metabolites [28]. Depending on the species, the release of TSH from PT may trigger upregulation of Dio2 expression (Soay sheep and Syrian hamster Mesocricetus auratus), downregulation of Dio3 expression (Siberian hamster Phodopus sungorus) or reciprocal regulation of both deiodinases (European hamster Cricetus cricetus and Fischer F344 strain rats) [2,19,20,43,45]. The balance between Dio2 and Dio3 determines local concentrations of T3 in the mediobasal hypothalamus (MBH) and hence seasonal changes in the activity of the hypothalamo-pituitary-gonadal axis.…”
Section: Introductionmentioning
confidence: 99%